La comunicación disruptiva en el modelo de negocio SAAS aplicado en las plataformas de streaming Netflix y Spotify - Avilés Cercado, Katherine Yamilex (2020)
The software as a Service (SAAS) as a business model, is nothing other than a distribution method that transmits the usual or traditional service in a custom digital service. In other words, this model helps companies improve their production through a method known as subscription and the accommodation in the cloud; In short, it is a process of innovation and transformation of the new digital age that certifies the facilitation and access to a number of various services through the web. For due process, the qualitative research was used, pretending the generation of concepts and theories that depart from previously studied works that served as a starting point to meet the objective of knowing the importance of the convergence between disruptive communication and the SaaS model that apply in Netflix and Spotify platforms, knowing the opportunities they provide.